The Impact of Linguistic Research Methodologies on Studying Languages’ System: A Critical Study - Ghanem, Salem Abood Mubarak (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2024)
The research aims to identify linguistic research methods and their impact on the study of the language system by examining the great service these methods have provided to scientific research in the linguistic aspect. In addition its  contribution, revealing the system of languages, their general and specific features, and their linguistic characteristics at their various levels. The multiplicity and diversity of linguistic research methods has had a great impact in enriching linguistic studies, and among the most prominent of those methods that the research will examine are: the historical method, the comparative method, the descriptive method, the generative-transformative method, the normative method, and the contrastive method.  Each of these methods has its own characteristics, its own fundamentals and its procedures, so the research aimed at identifying them, demonstrating their impact on the study of the language system, and their importance in rooting them, and defining their relationships and families to which they belong according to the characteristics, features, interests, and fields of each of those methods.